2008
DOI: 10.1007/s10803-008-0658-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Visuospatial Analysis and Self-Rated Autistic-Like Traits

Abstract: Although there is good evidence that the behavioral traits of autism extend in lesser form to the general population, there has been limited investigation of whether cognitive features of the disorder also accompany these milder traits. This study investigated whether the superiority in visuospatial analysis established for individuals with autism also extends to individuals in the general population who self-report autistic-like traits. In an initial study, students scoring high on the Autism-spectrum Quotien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 47 publications
6
54
1
Order By: Relevance
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 62%
“…One interesting direction for future research would be an investigation into the sensory processing of children with varying levels of autistic traits. Furthermore, it would be interesting to investigate whether the differences observed in those with high and low levels of autistic traits in behavioural studies (Grinter et al, 2009a;Grinter, 2009b;Stewart & Ota, 2008) and fMRI (Von dem Hagen, 2011) would also be found in children. In addition, it would be an important next step to determine whether self-reported sensory sensitivity actually corresponds to differences in threshold.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…For example, Grinter et al (2009a) showed that performance on the Embedded Figures Test (EFT) and the Block Design component of the Weschler Intelligence Scale is positively related to AQ score (see also Almeida et al 2010). Grinter and colleagues also showed high performance in the EFT along with weak global form and motion detection (Grinter et al 2009b). Together, these findings indicate that individuals reporting relatively more autistic-like traits share strong performance on these classic markers of visuo-spatial skill in autism (e.g., Shah and Frith 1983).…”
Section: Autistic Traits In the Typically Developed Populationmentioning
confidence: 97%
“…Most of this research has focused on the cognitivebehavioural characteristics found in ASD. Similar to diagnosed individuals Frith 1983, 1993), TD individuals with high-AQ scores are faster and more accurate on tasks measuring visuospatial ability, such as the Embedded Figures Test and the Block Design Task (Grinter et al 2009;Stewart et al 2009; but see Scheeren and Stauder 2008). In addition, they perform well on especially the visuospatial items of Raven's Advanced Progressive Matrices, indicating enhanced perceptual functioning (Fugard et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to studies examining the broad phenotype for social functioning, one study used both a regression and an extreme group approach (Jobe and White 2007), and three out of the seven discussed studies exclusively selected participants from the extreme ends of the distribution (Jameel et al 2014(Jameel et al , 2015Poljac et al 2013). This was also the case for 4 of the 10 cognitive, visuospatial, executive and motor function studies mentioned (Grinter et al 2009;Kunihira et al 2006;Poljac et al 2012;Stewart et al 2009) and for 9 of the 12 studies discussed in a meta-analysis specifically focused on visuospatial ability (Cribb et al 2016). Instead of using regression or a median split to include all participants, most of these studies examining the broad autism phenotype recruited several hundred participants and used extreme cut-offs or the upper and lower percentiles of these large databases to select TD individuals with respectively very high and very low AQ scores.…”
Section: Introductionmentioning
confidence: 99%